HUBUNGAN PENERAPAN KAWASAN WAJIB MENCUCI TANGAN DENGAN PERILAKU PERSONAL HYGIENE PEGAWAI PADA MASA PANDEMI DI KELURAHAN SEI KERA HILIR II MEDAN - Jon Piter Sinaga; Sri Sudewi Sitio; Yunita Syahputri Damanik (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2021)
Hands are one of the media where the entry of germs. One of the diseases that can be transmitted through hands is Covid-19. Minimizing the risk of disease transmission can be done by improving personal hygiene by washing hands, especially during this pandemic. This study is to analyze the relationship between the application of the mandatory hand washing area and the personal hygiene behavior of employees during the pandemic in Sei Kera Hilir II Village, Medan in 2021. This type of research is analytic with a cross sectional approach which is carried out by collecting data through questionnaires. Sampling with the Total Sampling technique as many as 25 respondents. Data processing with chi square test. Statistical tests show that of the 25 respondents in Sei Kera Hilir II Medan, there are 16 respondents (64%) who have good knowledge about the importance of implementing mandatory hand washing areas, 7 respondents (28%) who have sufficient knowledge about the importance of implementing mandatory hand washing areas and 2 respondents (8%) who have less knowledge about the importance of implementing mandatory hand washing areas. There are 9 respondents (36%) who have good personal hygiene behavior, there are 14 respondents (56%) who have sufficient personal hygiene behavior and there are 2 respondents (8%) who have poor personal hygiene behavior. From the results of the statistical test, the p value = 0.005 or <0.05. So from these results, H0 is rejected and Ha is accepted. This shows that there is a relationship between the knowledge variable about the application of the mandatory hand washing area and the personal hygiene behavior of employees in Sei Kera Hilir II Village in 2021. There is a significant relationship between the application of the mandatory hand washing area and personal hygiene behavior.